PERHITUNGAN KESTABILAN DENGAN ANALISIS BALI. PADA RUMAH PEMBANGKIT BAWAH TANAH PROYEK PLTA SINGKARAK SUMATERA BARAT - Fauzi, Achmad
Design for underground openings has differences compare with design for structures as well as buildings or bridges. In the underground opening designer always connecting with the original rock masses, who has specified material behaviors and more complicated. According to the excavation works for making the underground openings the redistribution stressed will exist from the original stressed and failure may occurred in the rock masses. The rock masses failure in case of extended fissure or discontinued plane in the rock masses and the main problem now is determine the rock strength. However even numerical methods are used in practical ,it is not an easy to predict the mechanical behavior with sufficient accuracy. This is due to the geological and geomechanical characteristics of rocks are differ from those predicted comparing to the real conditions infield. For this purpose field measurement are performed during construction to revise the input data used in design analysis,as well as to monitor the stability of the rock mass in the underground opening structure. In this thesis will calculated the stability of Underground Power House where located at Singkarak Hydro Power Project in West Sumatera. The calculation used back analysis technique based on displacement values from field measurement to evaluated conditions of the rock masses around underground openings. Concluding remarks from this thesis are the stability calculation for underground openings used back analysis procedures can minimize differences between rock mass behavior in the site and the prediction or initial design based on the laboratory test. In this case we can revised the original design to guaranteed the stability of underground opening structures.